2016
DOI: 10.1007/s13580-016-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of developing embryos of apricot (Prunus armeniaca L.)

Abstract: Apricot (Prunus armeniaca L.) is an important, nutritionally valuable agricultural crop. A scarcity of transcriptomic and genomic data hinders progress toward understanding the molecular events of apricot embryogenesis, which is the primary determinant of fruit yield and kernel quality. In this study, three cDNA libraries were sequenced using an Illumina/Solexa platform. We obtained 35,928,496, 40,656,940, and 35,970,214 clean reads from endosperm formation (LT-A), embryo development (LT-B), and mature embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…In this study, we have performed transcriptome analysis of leaves from 7 apricot accessions and obtained an average of 43,023 transcripts (N50: 1762 nt) for all accessions with a mean length 1095 nt. The results are compatible with recently published transcriptome analysis of apricots: Bai et al (2016) obtained 59,851, 57,163, and 54,792 contigs from three embryo samples of apricot with average contigs size exceeding 427 nt (N50 of 908 nt). Niu et al (2015) generated 124,070 contigs (N50: 1603 bp) with the mean length of 829.62 bp in Siberian apricot.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we have performed transcriptome analysis of leaves from 7 apricot accessions and obtained an average of 43,023 transcripts (N50: 1762 nt) for all accessions with a mean length 1095 nt. The results are compatible with recently published transcriptome analysis of apricots: Bai et al (2016) obtained 59,851, 57,163, and 54,792 contigs from three embryo samples of apricot with average contigs size exceeding 427 nt (N50 of 908 nt). Niu et al (2015) generated 124,070 contigs (N50: 1603 bp) with the mean length of 829.62 bp in Siberian apricot.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings are in agreement with previous results; Dong et al (2014) reported the highest assignments of transcripts of embryos of Siberian apricot to biological processes (54,667, 40.72%), followed by cellular components (51,551, 38.40%) and molecular functions (28,039, 20.88%). Similarly, GO assignment of transcripts sequenced from buds, leaves, stems, flowers, fruit pulp, and seeds of commercial apricot resulted in maximum hits to biological processes, followed by cellular components and molecular function (Bai et al, 2016). The highest hits were related to the biological process GO category, which may indicate that the analyzed tissues were undergoing extensive metabolic activities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This technology has been used to examine gene function in many fruit crops; however, to date there are only a few published transcriptome studies of apricot fruit. These have focused on pericarp tissue development [6], mining of simple sequence repeat (SSR) markers [7], the identification of genes associated with pistil abortion [8], comparative analysis of fruit development in interspecific and intraspecific hybrids [9], developing embryos [10], oil accumulation in seed kernels [11], and endocarp cleaving [12]. At present, the apricot genome sequence is not publicly available and related genomic resources, including information to enhance molecular breeding of apricot fruit, are somewhat limited.…”
Section: Introductionmentioning
confidence: 99%